WAYANG POTEHI: MAKNA RAGAM HIAS HEWAN PADA DEKORASI PANGGUNG PERTUNJUKAN - Trisna Widyani; Dyah Tjaturrini; Felix Sutanto (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. Tionghoanese is one of the societies who are really believes in myth and symbol. They believe that myth and symbol will influence their cultural and social life. Symbols that they use can be in form of color, animals, and plants. Each of them has meaning and can also represent and convey the message to the another society. These symbols usually are used in art performance related to the ritualistic activities, such as Wayang Potehi. Wayang Potehi is a one of traditional art of Tionghoanese that can be a means or media to preserve their existence. Hence, it is not suprising if their life, Tionghoanese always relate to the symbol meaning that they believe good for their life. Keywords: myth, symbol, ritual, media, existence